Feeding PAOB at different level of amino acids in the diet of broiler chickens - Goh, C. H.; Loh, Teck Chwen; Foo, Hooi Ling (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
The purpose of this study was to investigate the effect of dietary supplementation with organic acids (OA) with different level of amino acids on the growth performance, digestibility and microflora count in broiler chickens. The diet supplemented with organic acid and palm fat (POAB) in broiler diet showed an increase in body weight gain (2963.00 g) compared to control group (2694.55 g) at the end of 42 day of experiment. A similar trend was found for crude fat, methionine and lysine digestibility. It showed that the OAPF able to improve the nutrients digestion of the chickens. From the results, the OAPF able to improve the growth performance by increase the digestibility of the chickens. Moreover, the treatment groups supplemented with OAPF promote the growth of beneficial bacteria which was indicated by higher lactic acid bacteria (LAB) count compared to the treatment without organic acids.